Kajian Korupsi sebagai Proses Sosial: Melacak Korupsi di Sektor Sumber Daya Alam di Indonesia - Wigke Capri; Devy Dhian Cahyati; Mahesti Hasanah; Dias Prasongko; Wegik Prasetyo (Integritas: Jurnal Antikorupsi, 2021)
Corruption action develops way more advance compare to corruption studies in Indonesia. Corruption studies are mostly focusing on institutional corruption or using an institutional approach to understand corruption. This research offers to understand corruption better using actor-based and network approaches. Utilising social network analysis (SNA), researchers unpacking corrupt relational actors in natural resources, especially in oil and gas and forestry in Indonesia. We collected six important findings; corruption creates dependencies amongst actors; to be corrupt, an actor must have a strong network and resources that can offer and deliver multi-interests. Corrupt action is a repeated action that creates interlocking relations amongst actors. Interlocking relation serves as a safety belt for each chauffeur. Institutionalisation of corrupt networks only requires a strong corrupt network. The institutionalised corrupt networks shape a shortcut both for the private and public sectors-a short cut that makes bribery and exchange permits possible.